EFEKTIVITAS PROGRAM MAGANG DALAM MENINGKATKAN KETERAMPILAN KEWIRAUSAHAAN MAHASISWA PENDIDIKAN EKONOMI - Arya Alfareza, Andi; Haeril; Sahiruddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effectiveness of internship programs in enhancing students’ entrepreneurial skills. This research employed a quantitative approach with an ex post facto method, involving 43 Economics Education students of Muhammadiyah University of Bone who had participated in internship programs. Data were collected through questionnaires and analyzed using simple linear regression. The results revealed that all items of variables X and Y were valid, with correlation coefficients ranging from 0.333 to 0.792, exceeding the r-table value of 0.301 at the 5% significance level. The partial t-test showed a calculated t-value of 9.429, greater than the critical t-table value of 1.68385, with a significance level below 0.001. This proves that internship programs have a significant effect on students’ entrepreneurial skills. The correlation coefficient of 0.827 indicates a very strong relationship, with internship programs contributing 68.4% to students’ entrepreneurial skills. These findings emphasize that internship programs are an effective contextual learning medium for developing entrepreneurial competencies among students. However, their effectiveness can be further improved through intensive guidance and direct involvement of students in real entrepreneurial activities.